A survey on outlier detection methods in data mining - Thomas, Roy; E. Judith, J. (International Journal of Engineering and Technology, 2019)
Outliers are data objects whose characteristics differ from the mainstream characteristics of the data objects in a data set. Outlier detection plays a vital role in statistics as well as in data mining. Outlier detection effects to find out hidden and important information from large data sets. It has been a research field with diverse application areas for the past few decades. Outlier detection has been a topic of research in many fields like detecting malicious activity in cyber security, finding fake transactions in banking, detecting abnormality in medical data, identifying defects in industrial products etc. and various methods have been developed for detecting outliers. Most of the methods are developed specifically for certain applications while others are generic methods. Outlier detection methods are grouped into supervised, unsupervised and semi-supervised methods depending on the availability of class labels. Outlier detection methods can also be classified into statistical, proximity-based, clustering-based and classification-based depending on the type of data. We, in this paper, present the relative advantages and limitations of various methods used for detecting outliers. Â Â